2000
DOI: 10.1053/vc.2000.6499
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Protect the Brain During Cardiac Surgery

Abstract: Despite significant advances in cardiopulmonary by pass (CPB) technology, surgical techniques, and anes thetic management, central nervous system (CNS) com plications remain a common and costly problem after CPB. Stroke is often considered a rare and unprevent able complication of cardiac surgery. Recent studies have shown that through the use of echocardiography and historical risk stratification strategies, we can de fine which patients are at substantially greater risk for CNS injury. Through enhanced under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 96 publications
1
2
0
Order By: Relevance
“…The aim of our study was then to retrospectively review the data concerning adult patients who underwent coronary and/or valve surgery at our hospital during a 5.5-year period (1994±June 1999); during that period, in fact, both types of pump (roller and centrifugal) were used at our hospital at the same time by the same team of surgeons, anesthesiologists and perfusionists. Our study could show that factors related both to the preoperative clinical status of the patients and to operative and CPB features can affect the occurrence of major neurological complications; age at intervention, previous vascular surgery, previous neurological episodes, as well as longer CPB times were risk factors for adverse neurological outcomes of adult cardiac surgery patients, as previously described [13].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The aim of our study was then to retrospectively review the data concerning adult patients who underwent coronary and/or valve surgery at our hospital during a 5.5-year period (1994±June 1999); during that period, in fact, both types of pump (roller and centrifugal) were used at our hospital at the same time by the same team of surgeons, anesthesiologists and perfusionists. Our study could show that factors related both to the preoperative clinical status of the patients and to operative and CPB features can affect the occurrence of major neurological complications; age at intervention, previous vascular surgery, previous neurological episodes, as well as longer CPB times were risk factors for adverse neurological outcomes of adult cardiac surgery patients, as previously described [13].…”
Section: Discussionsupporting
confidence: 79%
“…To date, several studies assessed the effect of CPB-related variables on neurological outcomes in adult patients undergoing cardiac surgery; in particular, it could be demonstrated that longer CPB times [4,5] and severity of ascending aorta atherosclerosis [4,8] were strong predictors of perioperative neurological complications, while lack of arterial line ®ltration [9,12] and pH-stat acid±base management [10] could also increase the occurrence of postoperative central nervous system dysfunction. On the other hand, the possible effects of other CPB variables are still being debated, and the roles of temperature management (normothermic vs. moderately hypothermic perfusion), mean arterial pressure levels during CPB and type of perfusion (pulsatile vs. non-pulsatile) in affecting neurological complication rates have not yet been completely de®ned [13].…”
Section: Discussionmentioning
confidence: 99%
“…Techniques of cannulation and the conduct of CPB have been implicated in generating such emboli. 35 Animal data suggest that hyperglycemia at the time of cerebral injury aggravates its severity, increasing the size of infarction and cerebral edema. 36 As in the myocardium, cerebral hyperglycemia in the presence of no-flow ischemia is as-sociated with increased production and in the absence of washout, accumulation of intracellular lactic acid that leads to cell dysfunction or death 37 .…”
Section: Glucose and Insulin Influences On Heart And Brain In Cardiac Surgerymentioning
confidence: 99%